The right to abortion in Brazil: between attempts to regress and oppose - Damião, Nayara André; Carloto, Cássia Maria (Argumentum, 2023)
This article discusses the right to abortion as a reproductive right. In Brazil, the fight for this right has always been permeated by the dispute between conservatives and the feminist movement. While feminists seek the right to decide about their own bodies and lives, conservative interventions to prevent the right to abortion under any circumstances rely on the participation and alliances of religious sectors of the Catholic and Evangelical churches, linked to political parties. The analysis retrieves this argument from the 1940s and applies it to current conservatism and its attack on the right to abortion. The basis of the debate lies in doctoral research which identified the sophisticated strategies and the intensification of conservative actions employed to hinder the right to abortion, and the fundamental role of feminists in preventing regression and keeping alive the fight for the right to choose.Keywords: Reproductive rights. Abortion. Conservatism. Feminist Movement.